Classic Kaposi's Sarcoma (non-hiv-associated) of oral cavity: a case report - Marcelo Carlos Bortoluzzi; Ramon Cesar Godoy Gonçalves; Cristina Maria de Freitas Zanellato; Juliana Cama Ramacciato; Roberto de Oliveira Jabur (Universidade Estadual de Campinas, 2017)
Kaposi's sarcoma (KS) is a locally aggressive multicentric mucocutaneous malignant neoplasm. The aim of this article is to report and discuss the immunohistochemical profile of a rare case of classic primary Oral Kaposi's sarcoma presenting on the hard palate of a female patient which was non-HIV and was not immunocompromised.